Diseño de un sistema de gestión de seguridad y salud en el trabajo para la empresa quality service engineering s.a.s., en la ciudad de santa marta, de acuerdo a la resolución 0312 de 2019 (2024)
The main objective of this project is to diagnose the Occupational Safety and Health Management System (OSHS) under compliance with the Minimum Standards defined in Resolution 0312 of 2019 taking into account that this does not exempt the employer from not complying with the other Legal Norms in force for the company Quality Service Engineering S.A.S which seeks to improve physical well-being and workers.. Te initial diagnosis shows that the organization has a large part of the implementation of the Occupational Safety and Health Management System (SGSST), which translates into non-compliance with certain items of the Minimum Standards established by the Ministry of Labor. In addition, the Colombian Technical Standard GTC 45 establishes the hazard matrix that seeks to identify hazards and assess occupational risks by identifying unsafe acts and dangerous conditions at source, environment and individuals, by taking measures to improve the prevention of accidents at work and occupational diseases, for them, the socio-demographic aspects, health conditions and working conditions must be known, in order to have information on the current situation of the collaborators to promote estrategias of promotion and prevention in the organization, and to create a work plan where the action plan is established that allows to offer the company the reduction of cost, optimization of productivity and increase the profitability of the organization in a consistent and progressive manner, under the review of the PHVA cycle, establishing measurement indicators for the Management System